Surface characterisation and functional properties of modified diamond electrodes - Shpilevaya, I (2014)
In this work, the use of modified diamond as an electrode material with superlative physical and electrochemical properties was investigated in a number of electrochemical applications. The surface chemistry of three differing forms of diamond, namely boron-doped microcrystalline diamond, boron-doped diamond powder and detonation nanodiamond powder was modified utilising such strategies as hydrogen plasma treatment, reactive ion plasma etching along with various chemical treatments. The surface and functional properties of the modified diamond electrodes were studied using a wide spectrum of techniques. The electrochemical activity of these materials was concomitantly investigated in order to expand the knowledge of diamond electrochemistry and to establish an understanding of how the surface chemistry of these materials impacts their electrochemical performance. In the first study, the nanostructuring strategies of boron-doped diamond surface with platinum nanoparticles were developed. In particular, two types of diamond nanostructures were produced: one consisting of platinum particles located on the top of diamond nanorods, the other with platinum particles located in the bottom of diamond nanopits. For the first time, the experimental evidence proving the mechanism of the diamond nanostructuring process was reported. The electrochemical activity of these nanostructured diamond electrodes with regard to the electrochemical oxidation of glucose and methanol was investigated. In the second study, the relationship between the surface chemistry of three differing forms of diamond, including microcrystalline boron-doped diamond, boron-doped diamond powder as well as detonation nanodiamond powder, and the electrode fouling in the result of the adsorption processes in methyl viologen and anthraquinonedisulfonate solutions was investigated. The influence of two dissimilar surface terminations: hydrophobic H-terminated and hydrophilic O-terminated on the electrode performance was studied in detail. This work provides a useful insight on the likely reasons for the undesirable adsorption occurrence which may be experienced in many electroanalytical applications that utilise solid and powdered forms of diamond. The third project extends the discussion on the study of the diamond electrodes, modified with detonation nanodiamond and boron-doped diamond powders and investigates the electrochemical behaviour of these materials. In this work, charge transport within the diamond powder films, partition coefficients of different redox mediators along with heterogeneous electron transfer constants were identified. The chemical modification of these electrodes with platinum nanoparticles along with the mechanism of nucleation and growth of the latter were studied. The enhanced electrode performance with regard to methanol electrooxidation reaction was demonstrated. The fourth study investigates the preparation of nickel modified boron-doped diamond electrodes and ascertains the relationship between the surface chemistry of the modified diamond and the associated electrocatalytic performance of nickel nanoparticles in hydrogen peroxide and glucose electrooxidation. The fifth study reports on the development of a novel surface functionalization strategy, based on porphyrin and amide coupling chemistry, which allows the creation of hybrid biomimetic diamond interface that was used as the artificial β-alanine receptor.